Influence of Persistent Inflammation in Follow-Up Biopsies After Antibody-Mediated Rejection in Kidney Transplantation - Gaston J. Piñeiro (Frontiers Media S.A., 2021)
Background: Despite recent advances in immunosuppression treatment, antibody-mediated rejection (ABMR) remains the leading cause of kidney graft loss. Information about prognostic markers and the efficacy of treatment is scarce.Methods: Retrospective study with kidney recipients diagnosed an active ABMR from January 1, 2004 to December 31, 2019 to explore the influence of persistent inflammation in follow-up biopsies on graft survival after ABMR treatment.Results: About 116 patients were included. Active ABMR were treated with a combination of plasma exchange (PE), intravenous immunoglobulin (IVIg), rituximab, and steroids. At 6 months of treatment, 63 (54.3%) patients presented a stabilization or improvement in kidney-graft function. The effectiveness varied depending on the timepoint of the presentation between transplantation and rejection, which is lower for those with late ABMR (63 vs. 21% for early vs. late ABMR, respectively). Ninety patients (77%) underwent a control biopsy after ABMR treatment, from which 46 (51%) responded to the treatment. Microvascular inflammation (MVI) persisted in 64 (71%) biopsies, whereas tubulitis persisted in 17 (19%) biopsies. Death-censored graft survival at 1 year was significantly lower in patients with persistent MVI (86% vs. 95% without persistent MVI, P = 0.002), or with persistent tubulitis (44% vs. 66% without tubulitis, P = 0.02). In the Cox Regression analysis, the persistence of MVI [hazard ratio (HR), 4.50 (95%CI, 1.35–14.96), P = 0.01] and tubulitis [HR 2.88 95%CI (1.24–6.69), P = 0.01) in follow-up biopsies significantly increased the risk of graft failure.Conclusion: Persistent inflammation in follow-up biopsies after ABMR treatment was associated with an increased risk of graft loss, even without meeting Banff rejection criteria.Study Registration: Agencia Española de Medicamentos y Productos Sanitarios (AEMPS): 14566/RG 24161. Study code: UTRINM-2017-01.